Weather extremes : A spatio-temporal perspectives - RATHORE, L. S.; PATTANAIK, D. R.; BHAN , S. C. (MAUSAM, 2016)
Being mainly an agricultural country the economy of India and its growth mainly depends on the vagaries of the weather and in particular the extreme weather events. India with a land of unique climatic regime due to several characteristic features, including (i) two monsoon seasons (south-west and north-east) leading to drought & flood condition, active and break cycle of monsoon and also heavy rainfall leading to flash flood and landslides, (ii) two cyclone seasons (pre and post-monsoon cyclone seasons), (iii) hot weather season characterized by severe thunderstorms, dust storms and heat waves, (iv) cold weather season characterized by violent snow storms in the Himalayan regions, cold waves and fog. The socio-economic impacts of the extreme weather events such as floods, droughts, heavy rainfall, cyclones, hail storm, thunderstorm, heat and cold waves have been increasing due to large growth of population and urbanizations, which has led to greater vulnerability. A spatio-temporal analysis of these weather extremes over India will be very helpful to understand the vulnerability potential and to improve the forecast skill and use these forecasts in minimizing the adverse impacts of such weather extremes.